Paracas Geoglyphs at Cerro Ocucaje, Ica, Peru - Chuquihuaccha Huancahuari, Carls William (2021)
This article presents unpublished data from an Archaeological Landscape with the presence of figurative geoglyphs. The study synthesizes and discusses the photogrammetric results of the recent archaeological finds in Cerro Ocucaje, within the framework of the Geoglyphs of Ica Archaeological Project. During the Late Paracas period (about 370-200 BC) and even during the Paracas-Nasca or Initial Nasca transitional phase (200 BC-AD 90), figures were built on the slopes of low elevation stony hills, which until today can be appreciate as part of the animated landscape of the Ica desert.